Dual vaccination against IL-4 and IL-13 protects against chronic allergic asthma in mice - Eva Conde (Nature Portfolio, 2021)
Asthma is caused by hyperreactivity to benign antigens, with humoral immunity orchestrated by interleukin-4 (IL-4) and IL-13 being the key etiological factor. Here the authors show, in humanized mouse models, that dual vaccination against IL-4 and IL-13 induces their durable suppression ameliorate experimental asthma, and to hint clinical translation.